Rice Husk and Chicken Manure as Raw Materials for Bio-Charcoal Briquettes for Sustainable Energy Development - Hadiarto, Agus; Firdaus, Muhammad; Mejaya, I Made Jana; Hidayat, Yayat (Analisis Kebijakan Pertanian, 2025)
Using biomass from rice husk and poultry litter is one way to supply easier, cheaper, and more abundant raw materials for a sustainable energy system. This paper aims to estimate the potential of biomass from chicken manure and rice husk for solid fuels, i.e., bio-charcoal briquettes. Rice husk and chicken manure can be processed into bio-charcoal briquettes through pyrolysis. This article presents the literature review, potential, and prediction of rice husk and chicken manure biomass based on the secondary data using ARIMA. This article shows two different estimation methods of rice husk because, in 2018, BPS-Statistics Indonesia changed the previous Method to the Area Sample Framework (KSA). This article predicts that the availability of rice husk and chicken manure will steadily increase, indicating that investment in the bio-charcoal briquette business would be very prospective. It is also supported by increased national income as a proxy of household income. Demand for staple and animal food will increase, implying that rice husk and chicken manure will also increase to produce bio-charcoal briquettes. This paper also points out the challenges in developing a bio-charcoal briquette business, such as high investment costs, uncertainty in the supply of raw materials, and a lack of industrial capacity and infrastructure.